UPAYA PENGEMBANGAN HASIL PEMANFAATAN MANGROVE DI DESA TANJUNG REJO, KECAMATAN PERCUT SEI TUAN, KABUPATEN DELI SERDANG - Meilinda Suriana Harefa; Angel Berutu; Chintya Simarmata; Devi Anggriani Brs; Irma Lumban Gaol; Alam Syahputra (Jurnal Samudra Geografi, 2023)
The purpose of this study was to find out how the efforts were made to develop the results of the use of mangroves in Tanjung Rejo Village, Percut Sei Tuan Sub-district, Deli Serdang Regency. The population in this study is the Real Bakti KTH Group in the Mangrove Forest area of ​​Tanjung Rejo Village. The sample used in this study was to conduct interviews with the Head of the KTH Bakti Real Group, Mr. Salamin Yahya, the Head of the Srikandi Bakti Real Group, Mrs. Sakilah, and the Deputy Chairperson of the Srikandi Bakti Real Group, Mrs. Suryaningsih. The data collection technique used is field research, where the author goes directly to the field to obtain the necessary data. The results of the research conducted show that the development of mangrove products in this village is still not optimal, so it is necessary to make further development efforts, especially in the field of product marketing.